Prywatyzacja jako instrument poprawy efektywności gospodarki gminy - Zalewski, Alojzy (Privatization as an Instrument for Increasing Efficiency of Local Government Services, 2007)
The article attempts to analyze and assess the determinants of efficient privatization of local government services. The analysis includes the relationship between ownership and performance, possible impact of privatization on the economic efficiency, the experience of privatization of the British public utilities, and the determinants of efficient privatization of municipal services. These analyses have shown that the main reason to privatize should be to improve efficiency, both narrowly within the organization and more widely to improve the functioning of the economy for those industries that rely on enterprise services, and that efficient privatization of local government services depends on: - the possibility of introduction of competition into municipal services, - characteristic of service markets created - character of needs satisfied by local government services.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 203-214